Covert Texting During Simulated Driving Maneuvers: Effects of Head-Up versus Head-Down Posture. (September 2014) - Schieber, Frank; White, Samuel
The deleterious effects of distracted driving are pushing lawmakers to enact legal prohibitions against the use of text messaging services while operating a motor vehicle. However, in states where such prohibitions have been enacted the crash rate has actually increased. One possible explanation of this paradox is that prohibition laws may cause many drivers to conceal their text messaging behavior rather than eliminate it. Holding a cell phone out-of-sight to conceal texting behavior may be accompanied by prolonged loss of visual contact with the road resulting in a concomitant reduction in driving performance. An exploratory study was conducted to assess the effects of text messaging upon simulated driving performance. Sixteen participants performed the Lane Change Task (LCT) in a driving simulator under three experimental conditions: (1) baseline driving without texting, (2) texting while holding the cell phone at steering wheel level (head-up condition) and (3) texting while holding the cell phone out-of-view from other drivers (head-down condition). The efficiency of the required lane change maneuvers was significantly degraded while participants were engaged in text messaging behavior relative to the baseline driving condition. However, no evidence was found to support the hypothesis that attempts to conceal text messaging behavior (head-down condition) resulted in greater decrements to driving performance than texting without attempts at concealment (head-up condition). An important limitation of this study was that driving behavior was assessed only in terms of the efficiency of steering maneuvers. More sophisticated simulation protocols that assess hazard detection and avoidance behaviors may be more sensitive to the loss of situation awareness hypothesized to accompany attempts to conceal text messaging behavior while driving.